2019
DOI: 10.1007/s10916-019-1188-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Stress Response of a Paralympic Athlete During an Ultra-Endurance Event. A Case Study

Abstract: Psychophysiological response of athletes with spinal cord injurie has not been reported yet in scientific literature. The aim of this study is to examine the psychophysiological stress response of Paralympic athlete during competitive activities. We collected the following psychophysiological measurements: anxiety-trait, anxiety-state, locus of control, perceived psychological stress, stress-copying style, rate of perceived exertion, perceived muscle pain, body temperature, forced vital capacity, blood oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
1
23
1
Order By: Relevance
“…However, significant increases were found in isometric hand grip strength, which leads us to think that the greater sympathetic activation which occurs in this type of events (Belinchon-deMiguel and Clemente-Suárez, 2018), can lead to increases in muscle strength, as it has been shown in other stressful and extreme conditions, such a military contexts (Tornero-Aguilera et al, 2017;Tornero-Aguilera and Clemente-Suarez, 2018). This tendency was not similar with an ultra-endurance Paralympic athlete, where hand strength values decreased after an ultraendurance mountain event, probably due to the fact the upper body muscles were the principal implicated in this event (Belinchon-deMiguel et al, 2019).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…However, significant increases were found in isometric hand grip strength, which leads us to think that the greater sympathetic activation which occurs in this type of events (Belinchon-deMiguel and Clemente-Suárez, 2018), can lead to increases in muscle strength, as it has been shown in other stressful and extreme conditions, such a military contexts (Tornero-Aguilera et al, 2017;Tornero-Aguilera and Clemente-Suarez, 2018). This tendency was not similar with an ultra-endurance Paralympic athlete, where hand strength values decreased after an ultraendurance mountain event, probably due to the fact the upper body muscles were the principal implicated in this event (Belinchon-deMiguel et al, 2019).…”
Section: Discussioncontrasting
confidence: 62%
“…Another acute effect of this type of events is a decrease in muscle strength values, not generalized, since only the strength of the lower limbs was negatively affected, which is consequent with previous studies in similar ultra-endurance events (Belinchon-deMiguel et al, 2019), explained due to the higher implication of lower body muscles. However, significant increases were found in isometric hand grip strength, which leads us to think that the greater sympathetic activation which occurs in this type of events (Belinchon-deMiguel and Clemente-Suárez, 2018), can lead to increases in muscle strength, as it has been shown in other stressful and extreme conditions, such a military contexts (Tornero-Aguilera et al, 2017;Tornero-Aguilera and Clemente-Suarez, 2018).…”
Section: Discussionmentioning
confidence: 68%
“…Currently, in addition to all these factors, the COVID-19 pandemic appears as a new factor of uncertainty and lack of control, becoming a new stressor for Olympic and Paralympic athletes. Olympic and Paralympic athletes presented low psychological inflexibility, loneliness, and anxiety values, characteristic psychological profile of these population (Bond et al, 2011;Belinchón-deMiguel et al, 2019). Nerveless, athletes with lower studies (high school) presented higher psychological inflexibility than athletes with higher studies.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study we found how anxiety levels were in line with non-pathological population, showing no impact of the quarantine in the anxiety response of Olympic and Paralympic athletes. This fact could be related with the higher cognitive resources and large experience of these high-performance athletes in coping with anxiety contexts as competitions (Belinchón-deMiguel et al, 2019). These characteristics could be also explaining the high punctuation in conscientiousness personality factor, fact related with the aim of to control every aspect of training, nutrition, life... that can finally affect competition.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies in athletes with spinal cord injuries (SCI) focused on the analysis of strength, ergometry and mental well-being, showing that long-term and short-term physical training, improving physical and mental performance, is possible. When it comes to Paralympians, research focused on the study of mechanical performance, the effect of training upper body muscle endurance and the effects of interval training [43]. Havva (2019), in turn, conducted research of differences in fear of social appearance and self-esteem in athletes with and without disabilities.…”
Section: Discussionmentioning
confidence: 99%